Elaboración del plan de mantenimiento a los acondicionadores de aire split en el edificio Facultad Ciencias de la Ingeniería. - Baño Lisintuña, Kléber Fabián (2017)
Considering that technological advances have modernized us and provided many facilities and comfort, it is also true that they must be provided with adequate maintenance to prevent failures in their operation due to excessive use and exposure to severe environmental conditions. The Engineering Science Faculty, of the State Technical University of Quevedo, in its infrastructure has the installation of air conditioning equipment so that its community has an air-conditioned environment that allows to develop in a pleasant space. However, this Faculty does not have a technical department to maintain the equipment that regulates the ambient temperature and has to resort to the existing in the University who often provide a half service for lack of staff and time. The purpose of the research is to design a maintenance plan for the Faculty of Engineering Sciences and in this way you can perform the maintenance of existing air conditioners thus achieving a periodic technical check cheaper maintenance and prolong life Useful of air conditioners. In this research work a model of the maintenance plan is attached for its implementation. Keywords: Air conditioners, household appliances, types of maintenance, costs, technical catalogs, maintenance plan.